Speed-Related Energy Flow and Joint Function Change During Human Walking - Hu, Zheqi; Ren, Lei; Hu, Dan; Gao, Yilei; Wei, Guowu; Qian, Zhihui; Wang, Kunyang (Frontiers in Bioengineering and Biotechnology, 2021)
During human walking, mechanical energy transfers between segments via joints. Joint mechanics of the human body are coordinated with each other to adapt to speed change. The aim of this study is to analyze the functional behaviours of major joints during walking, and how joints and segments alter walking speed during different periods (collision, rebound, preload, push-off) of stance phase. In this study, gait experiment was performed with three different self-selected speeds. Mechanical works of joints and segments were determined with collected data. Joint function indices were calculated based on net joint work. The results show that the primary functional behaviours of joints would not change with altering walking speed, but the function indices might be changed slightly (e.g. strut functions decrease with increasing walking speed). Waist acts as strut during stance phase and contributes to keep stability during collision when walking faster. Knee of stance leg does not contribute to altering walking speed. Hip and ankle absorb more mechanical energy to buffer the strike during collision with increasing walking speed. What is more, hip and ankle generate more energy during push-off with greater motion to push distal segments forward with increasing walking speed. Ankle also produces more mechanical energy during push-off to compensate the increased heel-strike collision of contralateral leg during faster walking. Thus, human may utilize the cooperation of hip and ankle during collision and push-off to alter walking speed. These findings indicate that speed change in walking leads to fundamental changes to joint mechanics.